Role of insurance in place of aqilah in paying blood money resulting from accidents: an analytical study - Muhammad Husni, Ahmad; Omar, Anwar Fakhri; Alias, Muhammad Nazir; Samuri, Mohd Al-Adib (Medwell Journal, 2014)
Insurance is one of the most important contemporary issues emerging among Muslims because of its many concepts that a person needs to know. The legitimate, practical and applicable study of this concept, to see if this issue which has preoccupied minds of the Muslims for more than sixty years through international and meetings is compatible with the purpose of Islamic law and its foundation. The issue of payment of blood money from the insurance companies is considered as one of the most important emerging jurisprudential issues at the present time as the custom now is for people to ask for compensation only from insurance companies especially related to car accidents and the alternatives they have made through these councils when there is no ‘Aqilah’ or Baitulmal for Muslims or the inability of the ‘Aqilah’ itself to pay because of certain conditions or to what extent the Muslim community needs this kind of contracts. The study adopted inductive analytical approach to gather the views of scholars, researchers and their evidence and arguments on the subject and texts related to it and tried to analyse them with what suit our contemporary period and the purpose of Shariah. Furthermore, a practical and field approach was applied. The research found that there is a need for the insurance companies to stand in place of ‘Aqilah’ in the payment of blood money and there should be no difference between ‘diyyah’ (blood money) and compensation in terms of request and jurisdiction.